Identification of Object and Tourist Attractions for Agrotourism Development of High Potential Village in Batang Onang Sub-district - Putri Fikadilah Siregar; Tati Budiarti; Bambang Sulistyantara (Jurnal Lanskap Indonesia, 2023)
As an agricultural and tourism area, Batang Onang Sub-district has six villages with a high potential classification. Agrotourism promoted based on the relationship between agriculture and tourism. Agrotourism in this sub-district developed by integrating existing potential objects with agricultural activities to be a new tourist attraction. This study aims to identify potential objects and tourist attractions for the development of agrotourism in this sub-district. This study used Analysis of Potential Objects and Tourist Attractions (ODTW) and Analysis of Potential Objects and Natural Tourist and attractions (ODTW-A). The results showed that three villages have a high potential classification in Batang Onang Sub-district (50%) for agrotourism development while the other three villages have a low potential. There are natural attractions, historical/archeological tourism, and educational tours that can be integrated with agrotourism activities to be developed in this sub-district. This study concludes that the interested criteria for agrotourism are natural beauty, distance and travel time, supporting facilities, types of tourism activities, and accessibility which all have high values in agrotourism development. Each village that has high scores will be proposed for agrotourism development, while those with low scores will be proposed for supporting agrotourism development in this sub-district.